DEVELOPING THE COMPETENCE OF EARLY SCHOOL STUDENTS THROUGH INDIVIDUALIZATION OF EDUCATION - Tojiboyeva G. R.; Axmadova A. K. (Bright Mind Publishing, 2025)
This article is devoted to the importance of individualization of education in the development of the competence of younger schoolchildren. It analyzes the theoretical foundations of the individualized approach, the use of new pedagogical technologies to increase the effectiveness of education, and the results of this approach in practice. The study shows the advantages of methods that take into account the individual needs and abilities of students.
Keywords: Individualization of education, younger students, competence, pedagogical technologies, innovative approach.